Sulfoxaflor exposure reduces egg laying in bumblebees Bombus terrestris. Issue 1 (29th October 2019) - Siviter, Harry; Horner, Jacob; Brown, Mark J. F.; Leadbeater, Ellouise
Abstract: Sulfoximine‐based insecticides, such as sulfoxaflor, are of increasing global importance and have been registered for use in 81 countries, offering a potential alternative to neonicotinoid insecticides. Previous studies have demonstrated that sulfoxaflor exposure can have a negative impact on the reproductive output of bumblebee colonies, but the specific life‐history variables that underlie these effects remain unknown. Here, we used a microcolony‐based protocol to assess the sub‐lethal effects of chronic sulfoxaflor exposure on egg laying, larval production, ovary development, sucrose consumption, and mortality in bumblebees. Following a pre‐registered design, we exposed colonies to sucrose solutions containing 0, 5, 10 and 250ppb of sulfoxaflor. Exposure at 5 ppb has been previously shown to negatively impact colony reproductive success. Our results showed that sulfoxaflor exposure at 5 ppb (lowest exposure tested) reduced the number of eggs found within the microcolonies (Hedge's d = −0.37), with exposed microcolonies also less likely to produce larvae (Hedge's d = −0.36). Despite this, we found no effect of sulfoxaflor exposure on ovarian development. Sulfoxaflor‐exposed bumblebees consumed less sucrose solution, potentially driving the observed reduction in egg laying. Policy implications . Regulatory bodies such as the European Food Safety Authority (EFSA) are under increasing pressure to consider the potential impact of insecticides on wild bees, such as bumblebees, but sublethal effects can go undetected at lower‐tier testing. In identifying just such an effect for bumblebees exposed to sulfoxaflor, this study highlights that microcolony‐based protocols are a useful tool that could be implemented within an ecotoxicology framework. Furthermore, the results provide evidence for potentially negative consequences of pollinator exposure to an insecticide that is currently undergoing the licensing process in several EU member states. Abstract : Regulatory bodies such as the European Food Safety Authority (EFSA) are under increasing pressure to consider the potential impact of insecticides on wild bees, such as bumblebees, but sublethal effects can go undetected at lower‐tier testing. In identifying just such an effect for bumblebees exposed to sulfoxaflor, this study highlights that microcolony‐based protocols are a useful tool that could be implemented within an ecotoxicology framework. Furthermore, the results provide evidence for potentially negative consequences of pollinator exposure to an insecticide that is currently undergoing the licensing process in several EU member states.